KOMUNIKASI ORGANISASI KEHUMASAN POLRES PASURUAN - M. Alfin Fatikh; Redi Panuju (Jurnal Riset Komunikasi (JURKOM), 2018)
In reformation era and digitalization era now people increasingly free to uploade anything in social media. Begal case rampant in Pasuruan of east java to make people restless, when there is a perpetrator of Begal caught by public then recorded and then uploaded and the community who became victims of telling in the social media, so now Pasuruan called is "city of begal". The key to the success of public relations is the sense of security that people received through their online communication, a sense that will change the opinion of people who think Pasuruan "city of begal". The results of this research demonstrate the role definition of Pasuruan Police Public Relationship in providing security more dominant on communications technician and the role of expert prescriber to provide the succes information of the robber cyber team to build issues and opinions positive in society, but the communication facilitator and facilitator troubleshooter persists , though not so dominant. The application of the concept of service in online media is a form of commitment to the Police in providing security to the community. The quality of Public Relation communication with the online media communities needs to be improved, given the many people are talking about issues that occur in the online media.